The Impact of Both Individual and Collaborative Job Crafting on Spanish Teachers’ Well-Being - Consuelo Alonso; Samuel Fernández-Salinero; Gabriela Topa (Education Sciences, 2019)
Current changes in social structures and political-economic systems directly affect teachers’ job performance. Among others, these changes include changes in communication and information technologies, the scientific revolution, changes in the structure of populations, the revolution of social relations, economic and political transformations, and revolutions in labor relations and leisure time. These changes all seem to have promoted educational revolutions, which encourage the development of autonomous individuals who are capable of making critical judgments, ready to dialogue and cooperate in problem solving, and who seek alternatives aimed at building a better society. Thus, teachers suffer daily from the impact of continual changes that affect the way they do their work. According to the job-demands resources model, each job environment has its own characteristics that can be grouped into two dimensions: job demands and job resources. However, the relationship between job demands and resources has serious implications for individuals’ lives and psychological well-being. While work provides us with the means to survive, develop social relationships, and experience control over our lives, an excess of demands and a shortage of resources to cope with them would adversely affect personal well-being. Hence, individuals can perform behaviors through job crafting to balance this relationship between demands and resources at work. Job crafting is a proactive behavior of the worker who improves his own working conditions in order to achieve a more meaningful and satisfactory job. This phenomenon allows individuals to play a certain role by “creating„ their own job, changing the conditions in which they perform their tasks. In this study, 146 teachers participated to investigate the relationships between both individual and collaborative job crafting behaviors, on the one hand, and job satisfaction, work engagement, and teaching performance, on the other.